DESIGN AND DEVELOPMENT OF A LOW COST SEMI DIRECT TYPE COPRA DRYER - Eutiquio E. Sudaria (International Coconut Community Journal, 1993)
Coconut farmers in the Philippines use different types of copra dryer in copra processing. Copra quality and income are very much affected by the type of dryer used. In the country, there are indirect, direct, and semi‑direct type dryers. The common types of dryer used by the coconut farmers especially in the Visayas are direct and semi‑direct ones. There is high probability of the direct dryer together with the copra in getting burned because the firing place is directly under the drying platform where the coconut meat is placed. Especially if the meat is reaching 10% or lower moisture content where oil is coming out and the fire is immediately under it. Semi‑direct type dryer is quite comfortable to use having the less probability of burning the copra and the dryer because the firing place is away from the drying platform. The firing place is only linked to the drying platform by a tunnel.